KEBIJAKAN KRIMINALISASI TERHADAP PENYIDIK YANG TIDAK MENYEDIAKAN BANTUAN HUKUM KEPADA TERSANGKA YANG DIANCAM DENGAN PIDANA 5 TAHUN LEBIH BERDASARKAN PASAL 56 KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Wais Arfam Utama; Erdianto Erdianto; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Assistance by a legal adviser in a criminal justice process for a suspect ordefendant is very important because, even though his freedom is limited, a suspect still has human rights that are inherent in him and its fulfillment cannot be ruled out. The absence of legal consequences for violations of Article 56 of the Criminal Code is a factor in the emergence of crimes committed by law enforcement officials against suspects or defendants in the law enforcement process.The research method used in this thesis uses normative legal research, namely legal research which studies statutory regulations and legal principles. In this normative research, the writer conducts research on several laws and regulationsFrom the research, there are two main points that can be concluded. First, the criminal law policy against investigators who do not provide legal assistance to suspects who are punished with a sentence of 5 years or more is sometimes ignored or not in accordance with its purpose. Second, that an investigator who does not provide legal assistance to a suspect who is sentenced to 5 years in prison deserves to be qualified as an act that can be criminalized because he has violated several laws and other regulations.Keywords : Criminalization Policy, Investigators, Legal Aid